Thai Students’ Experiences of Learning English With a Non-Thai Teacher: a Phenomenological Study - Neiska Amanda Azrarianti; Pirman Ginting (Continuous Education: Journal of Science and Research, 2026)
This study looks into Thai students’ experiences of learning English with non-Thai teachers in primary and secondary schools in Thailand. Using a qualitative phenomenological research design, the study seeks to understand how students perceive, feel, and interpret their English learning experiences in communication-focused classrooms led by non-Thai teachers. The primary data source consisted of five interview participants aged 9-17, while a preliminary questionnaire administered to 21 students was used solely for contextual and screening. Data were gathered through semi-structured interviews conducted in English, each lasting around ten minutes. This was supported by a preliminary questionnaire given to a larger group of students for additional context. The researchers analyzed the data manually, following the steps set by Moustakas, which include bracketing, horizonalization, thematic clustering, and essence synthesis, while also drawing on van Manen’s interpretations. The findings highlight key themes regarding students’ emotional experiences, including enjoyment, excitement, fear of making mistakes, and shyness during speaking activities. While students typically reported feeling more motivated and comfortable when learning with non-Thai teachers, they also faced significant challenges, like anxiety and fear of judgment from their peers in speaking-centered classrooms This study adds to the limited research on primary and secondary EFL learners’ experiences with non-Thai teachers in Thailand and emphasizes the significance of emotional factors in English language teaching settings.